Followers dengan Kualitas Hubungan Pertemanan - Mario Mario (Institut Nalanda, 2023)
The theory used to look at the quality of friendship relationships is the theory of symbolic interaction, developed by George Herbert Mead and popularized by Herbert Blumer. In the theory of symbolic interactionism emphasizes the meaning that individuals give to social actions and the process of interacting with each other in forming social relationships. In a study on the effect of the number of Instagram followers of Hasanuddin University Psychology students Class of 2022 on the quality of the friendship environment, a quantitative approach was used through questionnaires given to respondents, which consisted of two variables collected, namely the number of followers Instagram (independent variable) and friendship quality (dependent variable). The sample used in this study is the Slovin formula and the margin of error is 10%, namely 55 students from a total of 121 Psychology students of Hasanuddin University Class of 2022 using the random sampling method. Based on the results of simple linear regression testing, it can be seen that the number of Instagram followers can cause a decrease in the quality of friendship relationships by 0.001 units. The follower count variable can explain the variable quality of friendship relationships by 0.3%.